Multi-level legitimacy: conceptualizing legitimacy relationships between the EU and national democracies - Achim Hurrelmann (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2006)
This paper deals with the ways in which the interconnectedness of multiple political levels in increaingly internationalized structures of governance impacts on these levels' democratic legitimation. Focusing on the European Union (EU), it argues that in the EU's multi-level system, the legitimacy of the European level of governance is systematically influenced by the legitimacy of the EU Member States. Insights into such legitimacy relationships - and different logics of their construction - can be used to identify a number of distinct legitimation strategies for EU institutions, and to sketch some options of institutional design that might help to implement them. It is unclear, however, to what extent any kind of institutional design can actually affect the citizens' empirical legitimacy evaluations of the EU, since these are often characterized by a lack of information about the EU's institutional structure.
Keywords: 320; EU-Politik; Welt; EU-Staaten